A Novel Cross-Linked Hemoglobin-Based Oxygen Carrier, YQ23, Extended the Golden Hour for Uncontrolled Hemorrhagic Shock in Rats and Miniature Pigs - Kuang, Lei; Zhu, Yu; Wu, Yue; Tian, Kunlun; Peng, Xiaoyong; Xue, Mingying; Xiang, Xinming; Lau, Billy; Tzang, Fei Chuen; Liu, Liangming; Li, Tao (Frontiers in Pharmacology, 2021)
Abstract Background: Hypotensive resuscitation is widely applied for trauma and war injury to reduce bleeding during damage-control resuscitation, but the treatment time window is limited in order to avoid hypoxia associated organ injury. Whether a novel hemoglobin-based oxygen carrier (HBOC), YQ23 in this study, could protect organ function, and extend the Golden Hour for treatment is unclear. Method: Uncontrolled hemorrhagic shock rats and miniature pigs were infused with 0.5%, 2%, and 5% YQ23 before bleeding was controlled, while Lactate Ringer's solution (LR) and fresh whole blood plus LR (WB+LR) were set as controls. During hypotensive resuscitation the mean blood pressure was maintained at 50 60mmHg for 60min. Hemodynamics, oxygen delivery and utilization, blood loss, fluid demand, organ function, animal survival as well as side effects were observed. Besides, in order to observe whether YQ23 could extend the Golden Hour, the hypotensive resuscitation duration was extended to 180min and animal survival was observed. Results: Compared with LR, infusion of YQ23 in the 60min- pre-hospital hypotensive resuscitation significantly reduced blood loss and the fluid demand in both rats and pigs. Besides, YQ23 could effectively stabilize hemodynamics, and increase tissue oxygen consumption, increase the cardiac output, reduce liver and kidney injury, which helped to reduce the early death and improve animal survival. In addition, the hypotensive resuscitation duration could be extended to 180min using YQ23. Side effects such as vasoconstriction and renal injury were not observed. The beneficial effects of 5% YQ23 are equivalent to similar volume of WB+LR. Conclusion: HBOC, such as YQ23, played vital roles in damage-control resuscitation for emergency care and benefited the uncontrolled hemorrhagic shock in the pre-hospital treatment by increasing oxygen delivery, reducing organ injury. Besides, HBOC could benefit the injured and trauma patients by extending the Golden Hour.